Labor Force and Supply Chains: Mutual Influence of Socio-Economic Factors (Republic of Kazakhstan) - Bakyt Beknazarov; Roza Niyazbekova; Saule Ilasheva; Olga Statsenko; Svetlana Turalina; Sapargul Yessenbekova; Sherzad Assilov (International Journal of Supply Chain Management, 2020)
Abstract— The Economic development increasingly requires sustainable supply chains of goods and services at the regional, national and global levels. Labor markets are as important as building the supply chain infrastructure; unbalanced labor market negatively affects supply chains by making them experience significant difficulties in hiring personnel necessary to ensure supply-chain sustainability. In turn, the labor market and its balance are influenced by a number of factors which are not fully reflected in available studies. This confirms the relevance of the present research. The purpose of the study is to investigate factors affecting labor force in the supply chain. Based on the comparative, didactic and descriptive analysis of regional and national demographic and socio-economic indicators, labor market indicators of the Turkestan region of the Republic of Kazakhstan as an indicative region, the study of national and international legislation, practices and literature related to supply chains and the labor market, the following results were obtained. The region is dominated by agricultural and industrial supply chains with a significant prevalence of the former. Despite the enormous agro-industrial, transport, resource, mineral and raw material, climatic, educational and labor potential of the region, the development of the region, the creation of new and development of existing supply chains are significantly hampered by a number of reasons, including inefficient and low-productivity agriculture, technological backwardness, and immobility of material and technical resources. Common factors affecting the labor surplus of a region (country) have been identified in the study based on the example of the given region. The major factors are a high natural and mechanical population growth rate; high growth rates of human resources that outstrip the growth rate of jobs; prevailing rural population; a deeper crisis in traditional industries and decreased enterprise demand for the labor force. The research methods and results will allow scientists and public officers to apply the information to design national and regional programs aimed at developing regions, creating regional, national and global supply chains, labor market development, including solving the problems of its imbalance and labor surplus.